Concomitant Transcranial Direct Current Stimulation With Ultrabrief Electroconvulsive Therapy: A 2-Week Double-Blind Randomized Sham-Controlled Trial. Issue 4 (December 2018) - Mayur, Prashanth; Howari, Rasha; Byth, Karen; Vannitamby, Rameswaran
Abstract : Objective: The feasibility and effectiveness of concomitant use of transcranial direct current stimulation (tDCS) with electroconvulsive therapy (ECT) has not been investigated. The study principally aimed at determining whether tDCS when combined with ECT improved the speed of antidepressant response. Secondarily, the ease of generation of seizures during electroconvulsive therapy and cognitive outcomes were investigated. Methods: Consecutive patients referred for ECT to treat major depression were randomized to tDCS with dorsolateral prefrontal electrode placements (n = 8) or sham (n = 8) used daily and just before thrice weekly, 6 times threshold, right unilateral ultrabrief (0.3 ms) pulse width ECT. Change of depression severity was determined using the Montgomery Asberg Depression Rating Scale along with cognitive assessments using Montreal Cognitive Assessment and visual memory testing at weeks 1 and 2, which were compared with baseline. Results: Change of depression severity from baseline was similar in tDCS and ECT compared with sham tDCS and ECT at week1 (mean [standard deviation SD] = 16.00 [6.78]; 13.75 [7.83]; P = 0.89) and at week 2 (mean [SD] = 23.00 [4.96]; 19.75 [9.85], P = 0.08). No between-group differences were obtained in the cognitive tests at weeks 1 and 2. Combining tDCS with ECT resulted in higher restimulation: 62.5% requiring 3 stimulations to achieve threshold in contrast to 12.5% with sham tDCS and ECT ( P = 0.04). The mean suprathreshold dose was higher in the tDCS and ECT group compared with sham tDCS and ECT: mean [SD] = 144.0 [43.54] and mean [SD] = 122.4 [20.36], P = 0.04, respectively. Conclusions: Concomitant use of tDCS with ultrabrief right unilateral ECT is feasible and safe albeit with higher rates of restimulation when tDCS was combined with ECT. However, there were no statistically significant differences in the speed of antidepressant response or cognitive outcomes at weeks 1 and 2 after the commencement of treatments.